Happy feet two : original motion picture soundtrack. - Powell, John, 1963- ([Place of publication not identified] : Sony Classical, 2011)
Songs are performed by the film's cast, which includes Pink and Robin Williams. Includes the spectacular medley from the opening scene.
Happy feet two opening medley (Pink, Common, Lil P-Nut, Happy Feet Two Chorus) -- The mighty Sven (Robin Williams, Hank Azaria, Happy Feet Two Chorus) -- Bridge of light (Pink, Happy Feet Two Chorus) -- Papa oom mow mow (Happy Feet Two Chorus) -- Dragostea din tei (Hank Azaria, Happy Feet Two Chorus) -- Erik's opera (Omar Cook, Eg Daily) -- Rawhide (Elephant Seal Chorus) -- Under pressure/Rhtymnation (Pink, Happy Feet Two Chorus) -- Tightrope (Ice cold mix) (Janelle Monáe, featuring Lil P-Nut and Happy Feet Two Chorus) -- In the hole ; Ramon and the krill ; Lovelace preshow (featuring Judith Hill) ; Searching for the kids ; The Doomberg lands ; I don't back up-- ; Trapped in emperor land -- Skua attack/Adelie rescue ; Dinner a la Sven ; We are the champions ; Snow stops play (featuring Steven Pence) ; No fly zone ; Krill joy ; Tappin' to freedom / (John Powell).
Various performers.
Hard copy version record.
Keywords: Motion picture music -- Excerpts; Popular music -- 2011-2020.; Motion picture soundtracks; Motion picture music; Songs; Streaming audio; Motion picture music -- Excerpts; Popular music; 2011-2020